Strategi green marketing: green awareness, eco label, dan eco brand pada perilaku pembelian - Utami, Kristiana Sri; Lestari, Dian; Maulana, Irfan (Universitas Widya Mataram, 2024)
In the midst of increasing discussions on environmental issues, more sustainable actions are becoming a matter of deep consideration. Sustainability has become a primary focus to be realized across various aspects of society, including in business. Environmental preservation issues challenge all companies to integrate these concerns into their business activities and corporate strategies. It is crucial for companies to develop eco-friendly products or services in hopes of reducing the impact of industrial activities on the environment. This study aims to examine the influence of green awareness, eco-label, and eco-brand as variables of green marketing on consumer purchasing behavior, using quantitative descriptive analysis on a sample of 165 randomly selected respondents. The data collected and processed are primary data. The study variables consist of a dependent variable, namely consumer purchasing behavior, and independent variables including green awareness, eco-label, and eco-brand. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) software, version 24. The analytical method used in this study is multiple linear regression. The analysis results indicate that green awareness, eco-label, and eco-brand significantly affect consumer purchasing behavior